Harnessing IGF-1 and IL-2 as biomarkers for calcineurin activity to tailor optimal FK506 dosage in α-synucleinopathies - Zaichick, Sofia; Caraveo, Gabriela (Frontiers in Molecular Biosciences, 2023)
Rise in Calcium (Ca 2+ ) and hyperactive Ca 2+ -dependent phosphatase calcineurin represent two key determinants of a-synuclein (a-syn) pathobiology implicated in Parkinson's Disease (PD) and other neurodegenerative diseases. Calcineurin activity can be inhibited with FK506, a Food and Drug Administration (FDA)-approved compound. Our previous work demonstrated a protective effect of low doses of FK506 against a-syn pathology in various models of a-syn related pathobiology. In this study, we present evidence that reducing calcineurin activity with FK506 in a-syn transgenic mice increased insulin growth factor (IGF-1), while simultaneously decreasing IL-2 levels in both cerebral cortex and serum. The highly conserved Ca 2+ /calcineurin signaling pathway is known to be affected in a-syn-dependent human diseases. FK506, an already approved drug for other uses, exhibits high brain penetrance and a proven safety profile. IL-2 and IGF-1 are produced throughout life and can be measured using standard clinical methods. Our findings provide two potential biomarkers that could guide a clinical trial of FK506 in PD patients, without posing significant logistical or regulatory challenges.